Bimbingan Kemampuan Berbicara Melalui Penerapan Pembelajaran Media Gambar Di Raudhatul Athfal Al-Huda Desa Sungai Tonang - Oki Rasdana; Tiara Andinie Paramitha Sisiliaudra; Diah Hananda Lumbanraja; Irend Gabriella; Ridho Maulana Asril; Suci Putriana Yanto; Ahmad Syuhada Gultom; Gesa Atras Faturrahman; Suryana Ardita; Nur Jamiah Lubis; Nurul Izzatil Madani (Pusat Riset dan Inovasi Nasional, 2024)
The research aims to improve children's speech skills through the implementation of image media learning at Raudhatul Athfal Al-Huda in Tonang River Village. The research method used is class action research (PTK) with Kemmis and McTaggart models. Data collection techniques using observation and documentation. The results of the study show that the implementation of the learning method of image media has a positive impact on children's speaking skills. There was a significant improvement in children's ability to describe objects in detail and specifically as well as in describing images. More than 89% of students achieved a significant improvement in speech skills after following this guidance. In conclusion, the implementation of image media learning is effective in improving speaking skills in Raudhatul Athfal Al-Huda, Tonang River Village. The suggestion of this study is to continue the application of this method by considering the needs and development of children in developing speech skills to improve language teaching approaches at an early age.